Charge susceptibilities of armchair graphene nanoribbon in the presence of magnetic field. (20th July 2016) - Rezania, H; Azizi, F
Abstract: We present the behaviors of both dynamical and static charge susceptibilities of undoped armchair graphene nanoribbon using the Green's function approach in the context of tight binding model Hamiltonian. Specifically, the effects of magnetic field on the the plasmon modes of armchair graphene nanoribbon are investigated via calculating the correlation function of charge density operators. Our results show that the increase of magnetic field makes the high-frequency plasmon mode for both metallic and insulating cases disappear. We also show that low-frequency plasmon mode for metallic nanoribbon appears due to increase of magnetic field. Furthermore, the number of collective excitation modes increases with ribbon width at zero magnetic field. Finally, the temperature dependence of the static charge structure factor of armchair graphene nanoribbon is studied. The effects of both magnetic field and ribbon width on the static charge structure factor are discussed in detail.